2019
DOI: 10.1371/journal.pone.0218081
|View full text |Cite
|
Sign up to set email alerts
|

Systemically transplanted mesenchymal stem cells induce vascular-like structure formation in a rat model of vaginal injury

Abstract: The beneficial effect of mesenchymal stem cells (MSCs) on wound healing is mostly attributed to a trophic effect that promotes angiogenesis. Whether MSCs can contribute to the formation of new blood vessels by direct differentiation is still controversial. Pelvic floor dysfunction (PFD) is a group of disorders that negatively affect the quality of women’s lives. Traditional vaginal surgical repair provides disappointing anatomical outcome. Stem cell transplantation may be used to supplement surgery and improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 70 publications
2
14
0
Order By: Relevance
“…Several studies have demonstrated that intravenously injected MSCs can migrate specifically to the sites of tissue damage, such as those caused by ischemic conditions or inflammation [46]. Even, it has been demonstrated that systemic administration of MSC was more efficient at all-time points for engraftment compared to after local MSC transplantation [47]. In addition, unlike other stem-cell-based therapies, MSCs do not require differentiation into a mature cell type prior to administration and have strong homing capacities in the damaged sites after cell transplantation [48].…”
Section: Mscs and Its Secretome In Intercellular Communicationmentioning
confidence: 99%
“…Several studies have demonstrated that intravenously injected MSCs can migrate specifically to the sites of tissue damage, such as those caused by ischemic conditions or inflammation [46]. Even, it has been demonstrated that systemic administration of MSC was more efficient at all-time points for engraftment compared to after local MSC transplantation [47]. In addition, unlike other stem-cell-based therapies, MSCs do not require differentiation into a mature cell type prior to administration and have strong homing capacities in the damaged sites after cell transplantation [48].…”
Section: Mscs and Its Secretome In Intercellular Communicationmentioning
confidence: 99%
“…In MSC-based therapy for PFDs, paracrine effects of MSCs play an important role in tissue regeneration through promoting the muscular cell survival [64], enhancing the host angiogenesis [58] and modulating the collagen metabolism [65]. Collagen metabolism disorder in connective tissues is one of the well-recognized pathogenic mechanisms of POP, and MSCs may regulate collagen metabolism via paracrine effect to optimize the functional characteristics of fibroblasts.…”
Section: Promotion Of Cell Survival or Trophic Effectsmentioning
confidence: 99%
“…Recently, Menachem-Zidon et al [58] reported a study evaluated the survival, differentiation and angiogenic effects of transplanted MSCs in a vaginal injury rat model established by vaginal incision. Remarkably, the systemically transplanted cells labeled with green florescent protein (GFP) migrated to vaginal injury site and survived for at least 30 days; furthermore, the transplanted cells acquired an endothelial phenotype in vivo, and they were detectable within capillary-like structures.…”
Section: Preclinical Studies Of Mscs-based Therapy For Pfdsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSC can be amplified in vitro and used for cell-based medical therapies because of their multi-lineage differentiation potential and ability to secrete factors associated with healing 14, 15. Showing promising results, the MSC based medical therapies has been reported on some disease types including vaginal injury, corneal alloimmunity, and spinal cord injury 16-18. Recently, it was found that MSC could be potential therapeutic cells for restoring erectile function in cavernous nerve injury (CNI) related ED rat models 19.…”
Section: Introductionmentioning
confidence: 99%